Đánh giá mức độ hài lòng của người dùng tin đối với chất lượng dịch vụ tại thư viện Trường cao đẳng sư phạm Thừa Thiên Huế - Hứa, Văn Thành (CĐSP Thừa Thiên Huế, 2016)
The research was conducted to measure and identify factors that influence student satisfaction about quality services of Thua Thien Hue College of Education Libary. The data was collected by direct interviews with 300 teachers and students who used services at this Liabrary. The descriptive statistics, Cronbach’s alpha test, Exploratory and Confirmatory Factor Analysis and Structural Equation Modeling were used in this study. The results show that the student satisfaction of quality services was positively influenced by three important factors, following in order as empathy, responsiveness and assurance. The results also reveal that several services need to be effectively informed to the students.